Effect of high wavelengths low intensity light during dark period on physical exercise performance, biochemical and haematological parameters of swimming rats - Wladimir Rafael Beck; Cláudio Alexandre Gobatto (2016)
Nocturnal rodents should be assessed at an appropriate time of day, which leads to a challenge in identifying an adequate environmental light which allows animal visualisation without perturbing physiological homeostasis. Thus, we analysed the influence of high wavelength and low intensity light during dark period on physical exercise and biochemical and haematological parameters of nocturnal rats. We submitted 80 animals to an exhaustive exercise at individualised intensity under two different illuminations during dark period. Red light (> 600 nm; < 15lux) was applied constantly during dark period (EI; for experimental illumination groups) or only for handling and assessments (SI; for standard illumination groups). EI led to worse haematological and biochemical conditions, demonstrating that EI alone can influence physiological parameters and jeopardise result interpretation. SI promotes normal physiological conditions and greater aerobic tolerance than EI, showing the importance of a correct illumination pattern for all researchers that employ nocturnal rats for health/disease or sports performance experiments.